2016
DOI: 10.1352/1934-9556-54.4.245
|View full text |Cite|
|
Sign up to set email alerts
|

Exploring the Self-Disclosure Process in Peer Mentoring Relationships for Transition-Age Youth With Developmental Disabilities

Abstract: Limited involvement of youth with developmental disabilities (DD) in mentoring programs has resulted in limited knowledge about the quality and impact of these relationships. The self-disclosure process has been identified as one factor impacting relationship development (Reis & Shaver, 1988). We proposed a theoretical model to examine the role of the self-disclosure process as a mechanism in peer mentoring relationship development for transition-age youth with DD by determining if selfdisclosure occurred, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…While the inclusion of these objectives supported relationship development in most dyads, we found in research reported elsewhere not all Project TEAM dyads established a meaningful mentoring relationship (Ryan, Kramer & Cohn, 2016). When coding mentor achievement of objectives for this feasibility study, we observed that some peer mentors focused on achieving call objectives to the detriment of relationship formation; these mentors tended to interpret discussion about personal experiences as ‘off topic’ rather than an opportunity to form relationships and improve overall mentoring outcomes.…”
Section: Discussionmentioning
confidence: 71%
“…While the inclusion of these objectives supported relationship development in most dyads, we found in research reported elsewhere not all Project TEAM dyads established a meaningful mentoring relationship (Ryan, Kramer & Cohn, 2016). When coding mentor achievement of objectives for this feasibility study, we observed that some peer mentors focused on achieving call objectives to the detriment of relationship formation; these mentors tended to interpret discussion about personal experiences as ‘off topic’ rather than an opportunity to form relationships and improve overall mentoring outcomes.…”
Section: Discussionmentioning
confidence: 71%
“…Other research indicates that in same-gender mentor relationships, the pairs are more likely to identify with each other, be more comfortable, and communicative [68]. For example, Ryan et al [69] found that in mentoring relationships with youths with developmental disabilities, the strongest connections included dyads where the mentee and peer mentor were the same gender. Ryan et al [69] also found that female mentees were more frequently in relationships with stronger connections as determined by mentor and mentee engagement and enthusiasm [69].…”
Section: Principal Findingsmentioning
confidence: 99%
“…For example, Ryan et al [69] found that in mentoring relationships with youths with developmental disabilities, the strongest connections included dyads where the mentee and peer mentor were the same gender. Ryan et al [69] also found that female mentees were more frequently in relationships with stronger connections as determined by mentor and mentee engagement and enthusiasm [69]. Further research should explore how a mentor's gender might influence the mentee's experience within a group-based environment.…”
Section: Principal Findingsmentioning
confidence: 99%
“…17,18 Moreover, during this stage of emerging adulthood, young adults are beginning to develop skills of self-determination, 19 and many young adults who have trusting relationships with mentors and/or support workers may feel more comfortable discussing topics of socializing, including bullying and dating, with them than they do with a parent or caregiver. 20,21 The current study aims to investigate the experiences and evaluate the acceptability and efficacy of an adapted version of the PEERS ® for Young Adults Program, 11 Mixed-methods program evaluations like this have been recommended for their capacity to demonstrate 'not only whether a novel intervention works, but also how and why, or why not', 22 p. 141.…”
mentioning
confidence: 99%